Cross‐sectional area reference values of nerves in the lower extremities using ultrasonography. Issue 4 (30th August 2014) - Seok, Hung Youl; Jang, Jae Hong; Won, Sun Jae; Yoon, Joon Shik; Park, Kyung Seok; Kim, Byung-Jo
ABSTRACT Introduction: Cross‐sectional area (CSA) reference values of lower extremity nerves using ultrasonography have only been reported in a few studies and have been limited to white populations. Methods: For this study, 94 healthy Korean volunteers were recruited for measurement of the CSA at 7 sites of lower extremity nerves. The side‐to‐side difference in CSA was calculated for each nerve, and reference ranges were derived. External validity evaluation for the reference values was performed with 10 newly recruited volunteers at a different institution. Results: Nerve CSA was correlated significantly with body mass index, weight, and height; however, the absolute value of the side‐to‐side difference had no significant correlation with demographic factors. The external validity was adequate for all sites, ranging from 80% to 100%. Conclusions: The lower extremity nerve CSA values obtained in this study may provide normal reference values for the Asian population. Muscle Nerve 50: 564–570, 2014